Managing a Pregnancy in the Presence of the Rare Blood Group Antibody PP1Pk - Bonmatí-Santané, Alexandra; Céspedes López, Roberto; Alvarez Saltos, Jehimy Jean; Calabia Martínez, Jordi; Noboa Paez, Cristina; Piedra Sánchez, Jordi; Visa Figueredo, Natalia; Maroto González, Anna (Women's health reports (New Rochelle, N.Y.), 2024)
Pregnant women with p phenotype, who lack antigens P, P1, and Pk, spontaneously form anti-PP1Pk antibodies whose primary target is the placenta. The risk of miscarriage in these women is 50%–70% and reaches 87% in the second trimester. The therapies aim to reduce the titer of antibodies early in pregnancy. They also have risk of hemolytic transfusion reaction, with very few compatible red blood cell donors in the world. In this study, we present a case of successful pregnancy managed with autologous blood donations and plasmapheresis.